Lugares amados, lugares sombra: éticas y estéticas en tiempos de transición - María Cecilia Roa García; Alejandro Quecedo del Val; Nils Lagrève; Ana Manuela Amaya Morales (Revista de Estudios Sociales)
Cañaverales, a community in southern La Guajira (Colombia), is at risk of becoming a shadow place, much like other villages that have vanished due to open-pit coal mining. These towns, disconnected from the national energy grid, have maintained close relationships with natural energy sources—such as the sun, wind, water, and food—despite the lifestyle changes brought by the use of fossil fuels. These connections, however, are steadily eroded by the encroachment of modernity. The disappearance of these traditional energy practices is a profound paradox: at a moment when the urgency to cease burning fossil fuels is clearer than ever, coal mining erases age-old energy practices that have thrived in simplicity, small scale, and ethical harmony with the land. This article explores this paradox through the lens of beloved places and shadow places. Cañaverales represents thousands of communities across the Global South that have sustained relationships of care, awe, reciprocity, and attunement with their territories—what we call beloved places. These communities resist being reduced to mere suppliers of renewable or fossil energy for distant regions, becoming instead shadow places. The extraction of coal from Cañaverales symbolizes the erasure and forced disappearance of these deep-rooted relationships with energy, transforming their ethics and aesthetics into memory and haunting specters of what once was.